LEGAL PROBLEMS REGARDING CONSUMER PROTECTION IN CLASS ACTION - ธรรมวินทร ฉัตรเฉลิม; กฤตยพงษ์ รุ่งแสง; เรืองวิชาธร จุมพิตา (Ratchaphruek Journal, 2017)
ABSTRACT This article aims to study and analyze the Act Amending Civil Procedure Code (No. 26), 2015, which sets out the criteria of class action and can be mutually applied with the Consumer Protection Act 2008 in order to make the proceeding of a large number of injured consumers more effectively. The results found that the criteria of class action regarding the person entitled to bring a class action, the costs and fees, the pursuit of additional evidence by the court, the objection of executing officer’s order in application for performance are not appropriate and do not correspond with the criteria of consumer protection. Furthermore, the class action cannot protect consumer to access to justice conveniently effectively. For this reason, if there has been a revision and amendment of the criteria of class action regarding the person entitled to bring a class action, the costs and fees, the pursuit of additional evidence by the court, and the objection of executing officer’s order in application for performance in correspondence with the criteria of consumer protection. Thus, the class action will be functioned to protect consumer to access to justice more conveniently.